2100. Nitroglycerin-Citrate-Ethanol Catheter Lock Solution Is Highly Effective in Eradicating Candida auris Biofilms. (26th November 2018) - Rosenblatt, Joel; Reitzel, Ruth; Vargas-Cruz, Nylev; Hachem, Ray Y; Chaftari, Anne-Marie; Dib, Rita Wilson; Kontoyiannis, Dimitrios P; Raad, Issam
Abstract: Background: Blood stream infections due to Candida auris is a significant public health concern due to increased patient mortality, frequent misidentification, and high rates of antifungal resistance. C. auris is known to be azole resistant, however several strains have been identified with elevated MICs to all classes of antifungals. Current treatment options for a pan-resistant strain of C. auris would be extremely challenging. Previously we have shown that non-antibiotic, Nitroglycerine + Citrate + Ethanol (NiCE) lock solution was highly efficacious in eradicating various species of multi-drug-resistant Candida. In this study we compared the efficacy of NiCE with standard of care antifungals commonly used in lock solutions in eradicating C. auris biofilms. Methods: Biofilm eradication of C. auris was evaluated in 10 strains. Candida auris biofilm was grown on silicone discs for 24 hours. Discs were then washed to remove any non-adherent organisms and exposed for 2 hours to various antifungal lock solutions including NiCE, Echinocandins, Azoles, and Amphotericin B. Discs were exposed to Muller–Hinton broth as a control. Subsequently discs were sonicated for 15 minutes in 5 mL of saline and quantitatively cultured onto sabouraud dextrose agar. Plates were incubated at 37°C for 48 hours and counted for growth. All testing was conducted with 6 replicates. Results: NiCE and Caspofungin were significantly more effective in eradicating C. auris biofilms compared with control ( P = 0.002 and 0.008, respectively). However, Caspofungin failed to eradicate a few strains of C. auris biofilm while NiCE completely eradicated all 10 strains. Micafungin, Anidulafungin, Fluconazole, and Voriconazole were not significantly different than control ( P > 0.05) for all strains. Conclusion: NiCE catheter lock solution was capable of completely eradicating all C. auris biofilms within 2 hours indicating high potential for preventing CRBSI caused by C. auris . Caspofungin eradicated some strains of C. auris biofilm, but failed to eradicate all. Other commonly used antifungals were no different than control. Future clinical studies to verify these findings need to be conducted. Disclosures: D. P. Kontoyiannis, Merck: Consultant, Research support and Speaker honorarium; Pfizer: Consultant, Research support; Astellas: Consultant, Research support and Speaker honorarium; Gilead: Speaker's Bureau, Speaker honorarium; F2G Inc: Speaker's Bureau, Speaker honorarium; Cidara Inc.: Speaker's Bureau, Speaker honorarium; Jazz Pharmaceuticals: Speaker's Bureau, Speaker honorarium. I. Raad, The University of Texas MD Anderson Cancer Center: Shareholder, Licensing agreement or royalty; The Unversity of Texas MD Anderson Cancer Center: Shareholder, Dr. Raad is a co-inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed to Novel Anti-Infective Technologies LLC, in which UTMDACC and Licensing agreement or royalty.